2015
DOI: 10.1007/s11104-015-2510-9
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophyte symbiosis alters nitrogen source of tall fescue host, but not nitrogen fixation in co-occurring red clover

Abstract: Background and aims Infection of tall fescue with the common toxic fungal endophyte Epichloë coenophiala harms livestock via toxic alkaloid production; therefore, non-toxic 'novel' strains of the endophyte have been developed and released. How different endophyte strains impact biological nitrogen fixation (BNF) in mixed species pastures is unknown. We asked whether novel endophyte or common toxic endophyte-infected (NE+; CTE+) tall fescue affects symbiotic and nonsymbiotic BNF, and utilization of biologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
2
9
1
Order By: Relevance
“…These results are consistent with previous work demonstrating the benefits of endophyte infection for tall fescue in diverse plant communities (e.g. Clay & Holah ; Bouton et al ; Rudgers et al ; Rudgers & Clay ; Slaughter et al ). However, our observed lack of endophyte infection effects on the species diversity or richness of the surrounding, developing plant community contradicts our second hypothesis and prior findings (Clay & Holah ; Rudgers et al ; Rudgers & Clay ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous work demonstrating the benefits of endophyte infection for tall fescue in diverse plant communities (e.g. Clay & Holah ; Bouton et al ; Rudgers et al ; Rudgers & Clay ; Slaughter et al ). However, our observed lack of endophyte infection effects on the species diversity or richness of the surrounding, developing plant community contradicts our second hypothesis and prior findings (Clay & Holah ; Rudgers et al ; Rudgers & Clay ).…”
Section: Discussionsupporting
confidence: 93%
“…Domestic livestock grazing is also present within tallgrass prairie restorations where tall fescue invasion is problematic in the United States, though tall fescue's influence on fire behavior has also been invoked as a mechanism driving invasion there (McGranahan et al 2012a). Endophyte infection may also increase the competitive ability of tall fescue relative to other plants (Clay & Holah 1999;Rudgers et al 2005;Slaughter et al 2016), although we found that the effects of endophyte infection on tall fescue did not affect the surrounding plant community. Perhaps the endophyte-associated effects on tall fescue and the surrounding plant community might have been more dramatic had domestic livestock grazing occurred in our prairie reconstruction.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, whether new endophytic strains have an impact on biological N 2 fixation in mixed species pastures is unknown. The results by Slaughter et al (2016) showed that endophytic strains produce different effects on tall fescue and nitrogen utilization. In mixed pastures, the deployment of novel endophytic strains to decrease alkaloid toxicity will differentially impact the use of biologically fixed N 2 in tall fescue and nitrogen concentration in red clover.…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 99%
“…The following five papers of this Special Issue emphasize the complexity of these interactions, and strongly suggest that the integrated knowledge of the role of endophytes in the aboveground food webs and nutrient cycling are very much in need to understand ecosystem functions. Slaughter et al (2016) examined whether novel endophyte or common toxic endophyte-infected tall fescue could affect symbiotic and non-symbiotic biological N 2 fixation, and utilization of biologically-fixed N 2 in tall fescue. Infection of tall fescue with the common toxic fungal endophyte Epichloë coenophiala is known as harming livestock via toxic alkaloid production, and the need of new non-toxic strains of the endophyte has been recently pointed out Kauppinen et al 2016;Saikkonen et al 2016).…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 99%